Exosomes and extracellular vesicles as liquid biopsy biomarkers in diffuse large B‐cell lymphoma: Current state of the art and unmet clinical needs. Issue 2 (18th November 2020) - Ofori, Kenneth; Bhagat, Govind; Rai, Alex J.
Abstract : Diffuse large B‐cell lymphoma (DLBCL) is the most common type of non‐Hodgkin's lymphoma, and it constitutes biologically heterogeneous entities. Standard first‐line therapies cure ~60% of patients, the rest being either refractory or experiencing relapse. Currently, there are no robust predictive biomarkers of therapeutic response. Heterogeneity of DLBCL is partly explained by the cell of origin (COO), ie, germinal centre B cell or activated B cell, with the latter exhibiting worse prognosis. While gene expression profiling (GEP) is the gold standard for determining COO, surrogate immunohistochemical algorithms are used clinically, but show significant discordance with GEP. Recently, additional genetic subgroups with different prognoses have been reported. However, the tools/expertise required for analysis prohibit widespread deployment. Liquid biopsy‐based assays show promise in providing clinically actionable information, are noninvasive and facilitate serial sampling to assess mechanisms of therapy resistance. Circulating, cell‐free DNA analysis has shown enhanced sensitivity for detecting molecular alterations, but this modality cannot determine alterations of the tumor proteome or on signalling pathways. Exosomes are endosomally derived vesicles, are found in high abundance in body fluids and are readily isolated using a variety of methods. Tumour‐derived exosomes can yield data regarding genetic, transcriptional, and proteomic changes useful for diagnosis, prognosis, and therapy of DLBCL. At present, standardized techniques for isolating exosomes are lacking and discriminating between exosomes from neoplastic and normal B cells is challenging. Refinements in isolation procedures are required to realize their full potential as precision medicine tools to provide comprehensive information on disease subtypes, identify prognostic factors, allow real‐time monitoring of therapy response and delineate novel drug targets.